CULTURAL WORKS POLITICS HETMAN PETER KONASHEVICH-SAGAYDACHNYY - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article revealed the role of Hetman Peter Sagaygachnyy in the development of Ukrainian culture and of the beginning of the XVI-XVII century covered national political aspect of the state and direction of its cultural politics.